CD4/CD8 ratio, comorbidities, and aging in treated HIV infected individuals on viral suppression. Issue 12 (30th April 2020) - Passos, Daniela F.; Bremm, João M.; da Silveira, Leonardo L.; Jantsch, Matheus H.; da Silva, Jean L. G.; Disconzi, Enzo; Rezer, João F. P.; Schwarzbold, Alexandre V.; Marques, Angela C. F.; Schetinger, Maria R. C.; Leal, Daniela B. R.
Abstract: The progression of the human immunodeficiency virus (HIV) infection to acquired immunodeficiency syndrome (AIDS) can be efficiently interrupted by antiretroviral therapy (ART). However, even successfully treated HIV‐infected individuals are prone to develop non‐AIDS‐related diseases that affect the metabolism and several organs and systems. Biomarkers that predict the occurrence of comorbidities may help develop preventive measures. Current research shows that CD4 + T cell counts and viral load do not predict the development of non‐AIDS‐related diseases. The CD4/CD8 ratio has been indicated as a suitable marker of persistent immune dysfunction and the occurrence of non‐AIDS‐related events in treated HIV‐positive patients. In this study, we explored the relationship between CD4/CD8 ratios, comorbidities, and aging in ART‐treated HIV patients on viral suppression. We collected and evaluated data from 352 HIV‐positive adults who were virologically suppressed (<40 copies/mL) on ART and with CD4 counts above 350 cells/mm 3 . The median age for participants was 46 years, 218 individuals had at least one comorbidity, and 239 had inverted CD4/CD8 ratios (<1). Current CD4/CD8 ratios were predicted by baseline CD4/CD8 ratios and nadir CD4 counts. Despite the high rates of inverted CD4/CD8 ratios and prevalence of comorbidities, no association between them was observed. The prevalence of comorbidities was significantly higher in older individuals, though aging alone did not explain the rate of all individual comorbidities. Low CD4/CD8 ratios were linked to neurocognitive disorders, suggesting that persistent T cell dysfunction contributes to neurocognitive decline. Highlights: Low CD4/CD8 ratios were associated with neurocognitive disorders in HIV infection. CD4/CD8 ratios were not associated with age in HIV infection. Aging and extremely low CD4/CD8 ratios were associated with the presence of comorbidities in HIV infection. Older HIV‐infected individuals are nearly three times more prone to develop comorbidities. The chance of having multimorbidity is nearly twice as high for older HIV‐infected individuals.